Implementation of Event and Experience Strategy in Marketing Communication at Tamo Venue Surabaya - Calysta, Keisya; Wono, Hilda Yunita (LPPM Stikosa - AWS, 2025)
The event and experience strategy are one of the applications of Integrated Marketing Communication (IMC) activities that allow direct interaction with consumers. This activity can also provide an interesting experience for consumers so as to increase brand recognition and business performance. Amidst the increasing demand for venue rental services to accommodate various events Tamo Venue, held a kids birthday showcase event which is an implementation of the event and experience strategy. This research is the first study to examine the experience strategy at children's events in the Surabaya venue industry. This study aims to explore how a newly established venue uses event and experiment strategy as a branding tool within the IMC framework. This research uses a qualitative case study method with data collection through structured interviews, documentation, and literature study. Interviews were conducted with the CEO, Head of event and marketing team, and an event attendee. Data was analyzed using NVivo 15 and validated through source triangulation. The results showed that Tamo Venue successfully implemented six strategic elements: alignment with MICE trends, original event concepts, non-repetitive execution, creation of tangible and intangible experiences, ambience and service quality, and an adaptive service approach. This research can enrich marketing communication studies by showing that event and marketing strategies can effectively create positive visitor experiences and offer practical guidance in the venue industry in Indonesia.